Análise microbiológica de cenoura e beterraba irrigadas com águas residuárias domésticas tratadas - Dantas, Iasmine Louise de Almeida (2015)
The use of treated domestic wastewater for irrigation could become an alternative to regions facing water scarcity, as in northeastern Brazil, specifically in the state of Sergipe. This work aimed to analyze the influence of the use of domestic wastewater treated in the microbiological quality of carrots (Daucus carota) and beets (Beta vulgaris) irrigated with this water. The experiment was conducted in a greenhouse of the Department of Agricultural Engineering (DEA) in the Federal University of Sergipe / Campus of Saint Kitts from April to July 2014. The wastewater was collected in the Sewage Treatment Plant (WWTP ) Rosa Elze, in the municipality of St. Kitts / SE. Irrigation was performed using four different dilutions. The evapotranspiration was obtained by the method of the Food and Agriculture Organization of United Nations (FAO) 56 through weather station mounted inside the greenhouse. The experimental design was randomized blocks (DBC), composed of eight treatments, two species and four wastewater percentage e/ou drinking water of Sergipe Supply Company (DESO); Of DESO 100% water; 75% water DESO + 25% waste water; 75% wastewater + 25% water DESO and 100% wastewater in five replicates and four plants per working portion. Microbiological samples were analyzed according to the parameters recommended by Resolution no. 12 02/01/2001 of the National Health Surveillance Agency - ANVISA: enumeration of fecal coliforms and Salmonella sp. In addition to these analyzes, they were also listed the population of mesophilic aerobic bacteria and molds and yeasts and the results were submitted to ANOVA by the Tukey test at 5% probability. The results obtained in the microbiological quality analyzes show that the beets and carrots irrigated with wastewater are in accordance with the standards established by law (Salmonella sp. Absence in 25 g fecal coliform ≤3 NMP. g-1) and the enumeration of mesophilic and molds and yeasts did not exceed 4,5x106, but we still need more depth to the thematic studies.